CONFLICT MANAGEMENT STRATEGY IN AN EFFORT TO INCREASE NURSE JOB SATISFACTION AT MAWADDAH MEDIKA HOSPITAL, MOJOKERTO - Basuki, Duwi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Conflict is one part that often occurs in the nurse's work environment. One of the conflicts that often occurs is with clients and colleagues. Prolonged conflict can disrupt a person's physical and mental health and needs immediate treatment. The aim of this research is to determine the relationship between conflict management strategies and nurses' job satisfaction at Mawaddah Medika Hospital, Mojokerto. The research design uses Correlation. The research sample was executive nurses who worked in the inpatient ward of Mawaddah Medika Hospital, totaling 31 respondents. The sampling technique used is proportional random sampling. The research results showed that conflict management strategies used integration strategies (compromise, collaboration and accommodation) were 71%. Statistical tests showed that there was a relationship between conflict management strategies and nurses' job satisfaction with ρ=0.02 with a strong category of relationship. The relationship pattern is positive, meaning that the better the use of integrated management strategies (compromise, collaboration and accommodation), the higher the nurse's job satisfaction. Efforts to improve the ability to handle conflict can be done with conflict management training, conflict handling roleplay with small group discussions.